2016
DOI: 10.1007/s10344-016-1054-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing human fear of wolves: moderating effects of geographical location and standpoint on protected nature

Abstract: This study analyses psychological antecedents of feelings of fear of wolves in a proportional sample of the Swedish population (national sample, n = 545) and in a sample of people in counties with wolf presence (regional sample, n = 1,892). Structural equation modelling of survey data suggests a dual pathway to selfreported fear. One path encompasses the appraisal of the environmental context operationalised as a potential wolf encounter. The second path concerns the appraisal of the social context assessed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Vulnerability was also directly addressed in the information content relating to the three relevant dimensions of CVM (predictability of brown bear behavior, controllability of personal reaction of being near brown bears, and danger in terms of risks and incidents), which likely affected the perceived coping potential in an encounter. Social trust, here operationalized according to the SVS-model, may be more difficult to establish as it was likely not only associated with the guides but also influenced by the organizations the guides represented and Swedish policy of brown bear management in general , Johansson, Sandström, Pedersen, & Ericsson, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability was also directly addressed in the information content relating to the three relevant dimensions of CVM (predictability of brown bear behavior, controllability of personal reaction of being near brown bears, and danger in terms of risks and incidents), which likely affected the perceived coping potential in an encounter. Social trust, here operationalized according to the SVS-model, may be more difficult to establish as it was likely not only associated with the guides but also influenced by the organizations the guides represented and Swedish policy of brown bear management in general , Johansson, Sandström, Pedersen, & Ericsson, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Such pattern can be explained by closer proximity to wildlife, but also more experiences of wildlife and wildlife damage in rural areas (Dressel et al, 2015;Eriksson et al, 2015;Jonker et al, 2006). Moreover, rural residents have been found to display a lower level of social trust in agencies responsible for managing wildlife, and more positive views of wildlife use and lethal control compared to urban residents (Johansson et al, 2016;Manfredo & Zinn, 1996). Additional conditions of importance for perceptions of wildlife and management include the community context and occupation (e.g., farming; Goodale et al, 2015;Klich et al, 2018;Liordos et al, 2017).…”
Section: Place Dimensions and Place-based Experiencesmentioning
confidence: 99%
“…To have a social network thereby seems to be a key component. In previous research on fear of large carnivores, social trust in managing authorities has been shown to reduce such negative feelings [29,37]. In the case of ticks there seems to be little controversy, why social trust may be of less relevance.…”
Section: Disease Levels Experience and Appraisalsmentioning
confidence: 97%